Capillary malformations: clinical review. - Wollina, U.; Chiriac, A.; Chiriac, A.E.; Koch, A. (European Journal of Pediatric Dermatology, 2025)
Capillary malformations (CM) are congenital vascular anomalies that occur in up to 2% of newborns without gender differences. They are the result of somatic mutations, most often in the GNAQ gene. While isolated CM have a good prognosis, syndromic CM can have a significant negative impact on quality of life. Careful clinical examination of cutaneous CM highlights the possible risk of neurological and ocular complications. In the current work, frequent and less frequent syndromic CM are described and their clinical and laboratory data are discussed. After discussing the differential diagnosis of CM, the available treatment options are reviewed, which include laser, photodynamic therapy, topical immunosuppressants, surgery and new targeted therapies. Finally, the need for a multidisciplinary approach in syndromic CM is emphasized.